Inner zone terrain correction calculation using interpolated heights - ZAHOREC, Pavol (Contributions to Geophysics and Geodesy, 2015)
The discrepancy between real heights of gravity points and the elevation model has a significant impact on the terrain corrections calculation especially within the inner zone. The concept of interpolated heights of calculation points used instead of measured ones within the specified inner zone can considerably decrease the resulting errors. The choice of appropriate radius of the inner zone for use of interpolated heights is analysed on synthetic topography model as well as real data. The tests with synthetic models showed the appropriate radius of this zone is proportional to the deformation wavelength of the model. Simple statistical analysis of a particular elevation model can give an estimate of the appropriate radius for the calculation using interpolated heights. A concept with interpolated heights in the zone 0–250 m is used in actual practice in Slovakia. The analysis of regional gravity data from the Tatry Mountains test area indicates the searched radius should be about 100 m. Detailed gravity measurements from different areas showed the searched radius does not play so important role but the use of interpolated heights instead of measured ones is still relevant. The more reasonable method instead of using interpolated heights is also presented when calculating the topographic effect.